Insights into the fabrication and structure of plutonium pyrochlores. Issue 5 (20th January 2020) - Finkeldei, S.; Stennett, M. C.; Kowalski, P. M.; Ji, Y.; de Visser-Týnová, E.; Hyatt, N. C.; Bosbach, D.; Brandt, F.
Abstract : Experimental & theoretical insights into the structural response of complex oxides to dopant elements – the example of plutonium within pyrochlore. Abstract : Rare earth zirconates, such as Nd2 Zr2 O7, crystallise with the pyrochlore structure and are a group of materials which have been suggested as potential nuclear waste forms for actinide immobilisation. In this work, a new hydroxide co-precipitation route is presented to investigate the incorporation of Pu into Nd2 Zr2 O7 . The plutonium content was varied between 5 and 10 mol% and the structural uptake and Pu oxidation state were probed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray absorption spectroscopy (XAS). The experimental findings were complemented by DFT ab initio calculations. For all the incorporation mechanisms studied PuO2 was used as the reference reactant state to allow for a direct comparison between the possible Pu uptake scenarios. Analysis of the experimental data suggests that Pu(iv ) cations substitute for Nd(iii ) cations leading to structural distortion of the pyrochlore A-sites. The computed solution energies and bond-distances corroborate the experimental findings and indicate that the excess charge is balanced via the introduction of oxygen at formerly vacant sites.